Estimates of Infection and Mortality From Covid-19 in Care Homes For Older People in Brazil - Patrick Alexander Wachholz; Virgilio Garcia Moreira; Déborah Oliveira; Helena Akemi Wada Watanabe; Paulo José Fortes Villas Boas (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To describe infection and mortality rates associated with COVID-19 in older people living in Brazilian care homes. METHODS: A descriptive cross-sectional study was conducted using primary and secondary data sources. Nationwide care home administrators were invited to report, via an online questionnaire, the occurrence of infection and mortality associated with COVID-19 from April to August 2020. State Public Prosecutor Offices, State Health Departments, and the Unified Social Security System were also contacted for information. Data were analyzed using descriptive statistics. RESULTS: Data were collected from 2154 care homes located in 14 states, covering 59 878 older residents. The incidence rate of COVID-19 was 6.57%, and 883 deaths were recorded in the period, with a case-fatality rate of 22.44%. CONCLUSIONS: The incidence and mortality rates observed in this study were lower than those observed in other (high-income) countries. Data sources related to COVID-19 outbreaks in Brazilian care homes are currently limited to self-report. Structuring and systematizing data recording and reporting in these settings is essential to better understand the spread of the virus and to protect care home residents in Brazil.